(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Ukrainian society of participants in the discussion of changes included in public, public and public discussions. Religion in connection with reports of transformations has become a full-fledged sector of the economic sphere. The creation of the analysis of relations in Ukraine coincided with the foundation and time of the development of theological views in the field of economics. Probably, civilizational processes are connected with the Christian Church and take on new forms. n different religious traditions, entrepreneurship is valued differently, and different patterns of business activity are formed. Cultural tradition influences the formation of the environment in which business is conducted, various aspects of economic behavior[15]. The state must move through the creation of fair economic institutions. Such institutions cannot be organized in a cultural vacuum, they need a living ethos of culture, which can appear only in the process of formation and approaching the ideal of a just society. It is important that moral and cultural institutions perform well their tasks in the economic sphere. Therefore, it is necessary to reveal the interaction of religion and society, to identify prospects and possible ways to improve it. The rethinking of religion and its involvement in social processes is taking place all over the world. Religious values and their influence on the formation of cultural, social and economic relations in society are studied. The world experience of interaction between religion and the state is studied. In today’s world, the importance of religious beliefs can act as a catalyst for socio-economic change[11].